2021
DOI: 10.3390/ijms22020945
|View full text |Cite
|
Sign up to set email alerts
|

ABT-751 Induces Multiple Anticancer Effects in Urinary Bladder Urothelial Carcinoma-Derived Cells: Highlighting the Induction of Cytostasis through the Inhibition of SKP2 at Both Transcriptional and Post-Translational Levels

Abstract: The objective was to investigate the anti-cancer effects and underlying molecular mechanisms of cytostasis which were activated by an anti-microtubule drug, ABT-751, in two urinary bladder urothelial carcinoma (UBUC)-derived cell lines, BFTC905 and J82, with distinct genetic backgrounds. A series of in vitro assays demonstrated that ABT-751 induced G2/M cell cycle arrest, decreased cell number in the S phase of the cell cycle and suppressed colony formation/independent cell growth, accompanied with alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…ABT-751, an anti-microtubule drug ( Table 1 ), has been reported to inhibit SKP2 transcription by suppression of the AKT serine/threonine kinase–nuclear factor kappa B signaling pathway and to downregulate stable/phospho-SKP2 post-translationally by inhibition of AKT signaling in the urinary bladder urothelial carcinoma cell lines BFTC905 and J82 ( Dehghanian et al, 2021 ) ( Table 2 ).…”
Section: Synthetic Small-molecule Skp2-inhibiting Compoundsmentioning
confidence: 99%
“…ABT-751, an anti-microtubule drug ( Table 1 ), has been reported to inhibit SKP2 transcription by suppression of the AKT serine/threonine kinase–nuclear factor kappa B signaling pathway and to downregulate stable/phospho-SKP2 post-translationally by inhibition of AKT signaling in the urinary bladder urothelial carcinoma cell lines BFTC905 and J82 ( Dehghanian et al, 2021 ) ( Table 2 ).…”
Section: Synthetic Small-molecule Skp2-inhibiting Compoundsmentioning
confidence: 99%
“…It has also undergone phase I and II trials for paediatric neuroblastoma (NCT00436852), which found ABT-751 to be well tolerated but not associated with increased objective response rate or time to progression [ 23 ]. Recent pre-clinical studies have examined ABT-751 as a potential treatment for urinary bladder urothelial carcinoma and p53-deficient hepatocellular carcinoma [ 24 , 25 ]. ABT-751 has a similar mechanism of action to the taxanes, but while the taxanes are substrates for P-gp, a study using an in vivo xenograft model suggests that ABT-751 is not [ 26 ] and can overcome P-gp-mediated resistance.…”
Section: Introductionmentioning
confidence: 99%